Local solutions for transformative development and sustainable futures - Gadu, Siyaxola; Maviza, Gracsious; Maphosa, Mandlenkosi (2025)
Members of the CGIAR FOCUS Climate Security Team in Southern Africa attended the 2025 NUST-WFP National Symposium in Zimbabwe, themed “Building Resilient Communities for Sustainable Futures.”. The symposium brought together officials from various government ministries, academia, development partners, and civil society organisations.